Analisis Kinerja Algoritma Hash pada Keamanan Data: Perbandingan Antara SHA-256, SHA-3, dan Blake2 - Sinaga, Joice Sharon Gabriella; Nehemia Sitorus; Steven Lukas Samosir (LPPM-ITEBA, 2024)
Data security is an essential aspect in the dynamic digital age, including protection of data integrity, confidentiality and authentication. This research evaluates the performance and security of three popular hash algorithms: SHA-256, SHA-3, and Blake2. Resistance to brute force attacks, avalanche effects, and processing time efficiency were analyzed. Results show that all algorithms have excellent resistance to brute force attacks, thanks to the 256-bit hash length. In terms of avalanche effect, SHA-3 shows higher consistency than the other algorithms, making it superior in maintaining data integrity. In terms of processing time efficiency, Blake2 performed best with the fastest hashing time, while SHA-256 offered balanced efficiency for general applications. SHA-3, although slower, has advantages in security and resistance to collision attacks. Overall, SHA-3 is recommended for applications with high security requirements, Blake2 is suitable for applications that prioritize efficiency, and SHA-256 remains relevant for applications that require a balance between speed and security.